Strategic Financial Management of Organizers of Classical Music Performances - Pilkytė, Rūta (Vilnius University Open Series, 2022)
The future of the classical music is uncertain both in Lithuania and the world. The very ability of this genre to withstand changing trends, financial needs, ability to retain and find new audiences is in question. Organizations that sell classical music are forced to look for additional sources of funding. The differences in sources of funding used by organizations may be explained by the political and legal environment, traditions of art patronage and other support (also, the willingness to ask for such a support), and the availability of fundraising resources. Ensuring the scope of funding sources is identified as a key task during the strategic financial management of classical music performance organizers, along with other stages of management that could lead to more efficient operations. The method of scientific literature and document analysis was used in this work. The research was concluded by stating that strategic financial management in organizations performing classical music includes: 1) the organization’s adaptation to the external environment; 2) getting ready for decision-making which is necessary to ensure adequate financial resources of the organization and their efficient use, taking into account the mission and objectives of the organization; 3) the implementation of the strategy (organizing events); 4) financial control and analysis.